Evaluasi Kondisi Jalan Lingkungan Rumah Sakit Umum Dr. Kanujoso Djatiwibowo Balikpapan - Rahmat Rahmat; Martheana Kencanawati; Suheriah Muliadevi (Abdimas Universal, 2019)
Road maintenance is to maintain road conditions that are in accordance with the level of service and capabilities when the road is completed and operated until the specified age of the plan is reached. Starting from these conditions, road maintenance needs to be carried out continuously / routinely and continuously. Handling road maintenance can be done regularly or periodically. Road maintenance is routinely carried out continuously throughout the year and is carried out as soon as possible when the damage has not been widespread. Care and repairs carried out at the stage of damage are still mild and local. This is done in connection with the relatively low repair costs and how to fix it is relatively easy / light. Environmental conditions of the Regional General Hospital Dr. Kanujoso Djatiwibowo currently (existing) using concrete pavement (rigid pavement) where the neighborhood Road General Hospital Dr. Kanujoso Djatiwibowo is overgrown with a lot of floating vegetation / water plants found during field monitoring. From the results of observations on Jalan Lingkungan, it is also surrounded by reeds and vines so that the impression is slum and not maintained. Keywords: Road maintenance, concrete pavement